Impact of Emotional Intelligence on Sustainable Leadership: A PLS-based Study - Munira, Kazi Sirajum; Rahman, Dr. Md. Sahidur; Akhter, Suchana (Business Perspective Review, 2022)
Purpose: The study aims to evaluate the impact of emotional intelligence (EI) on the sustainable leadership of managers in the context of Bangladesh. Emotional intelligence is made up of five components, viz. self-awareness, self-regulation, motivation, empathy, and social skills. Methods: This is a quantitative study based on survey data. Data were collected from the managers (n=262) working in different organizations located in Dhaka and Chittagong region by using the convenience sampling technique. EI was measured with 30 items adopted from the EQ Index (Rahim et al., 2002, 2006), while sustainable leadership was measured with 15 items adopted from the SLQ (McCann & Holt, 2010). PLS-SEM was applied to analyze the data and evaluate the measurement and structural models. Results: The findings suggest that managers’ emotional intelligence significantly influences sustainable leadership. Originality: This study is a pioneering study in the context of Bangladesh and it contributes to our understanding of the impact of emotional intelligence on sustainable leadership, which in turn, enhances managers’ sustainable performance. Limitations: The use of the convenience sampling technique may limit the generalizability of the findings.